Analysis of competitiveness of sugarcane farming: A case study in Kampung Beru Village, South Sulawesi - Bakri, Suardi; Afriana, Hana; Mahmud, Musdalipa; Ibrahim, Helda; Qurniasty, Qurniasty (Publisher of Widyagama University of Malang (UWG Press), 2023)
The sugarcane based sugar industry is a source of income for sugarcane farmers and workers in the industry. However, farmers often complain about the high price and cost of farming, which result in a decrease in the quality of sugarcane. The survival of sugarcane farmers is threatened, including those in Kampung Beru Village as one of the largest suppliers of sugarcane for Takalar Sugar Factory. This study aims to explore the competitiveness of sugarcane farming based on competitive and comparative advantages. Data collection was carried out through interviews and focus group discussion (FGD) involving 76 farmers. Policy analysis matrix (PAM) was utilized for data analysis. The results showed that the private cost ratio (PCR) value, an indicator of competitive advantage, was 1 (1.048), suggesting that sugarcane farming does not have a competitive advantage. Domestic resource cost ratio (DRCR) as an indicator of comparative advantage had a value of 1 (1.795), indicating that sugarcane farming also has no comparative advantage. Sugarcane farming has extremely low competitiveness. Hence, the government is advised to increase sugarcane productivity by conducting campaigns to use superior seeds, increase the efficiency of production facilities, revise purchase price standards, and regulate the marketing system.JEL Classification A10; B40; B55